2018
DOI: 10.1007/s00422-018-0752-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of long-range coupling in crayfish swimmeret phase-locking

Abstract: During forward swimming, crayfish and other long-tailed crustaceans rhythmically move four pairs of limbs called swimmerets to propel themselves through the water. This behavior is characterized by a particular stroke pattern in which the most posterior limb pair leads the rhythmic cycle and adjacent swimmerets paddle sequentially with a delay of roughly 25% of the period. The neural circuit underlying limb coordination consists of a chain of local modules, each of which controls a pair of limbs. All modules a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…While it is useful to compare control of these wavelike motions to that of other species it is also necessary to recognize that control of cephalo-caudal wave propagation by CPGs to produce undulating waves along the spine of animals such as Lamprey [31], and salamander [38] amphibians, quadraped mammals, and primates. Indeed this review has revealed organizational models with commonalities among species including Lamprey [31], salamander [38] and crayfish [39][40], and in mammals such as rats [33,42], mice [43] and cats [30,34]. suggested a 'temporal grid'.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While it is useful to compare control of these wavelike motions to that of other species it is also necessary to recognize that control of cephalo-caudal wave propagation by CPGs to produce undulating waves along the spine of animals such as Lamprey [31], and salamander [38] amphibians, quadraped mammals, and primates. Indeed this review has revealed organizational models with commonalities among species including Lamprey [31], salamander [38] and crayfish [39][40], and in mammals such as rats [33,42], mice [43] and cats [30,34]. suggested a 'temporal grid'.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang et al[30] used computational fluid dynamics in conjunction with a neural model of CPG circuits to show that a locked phase difference between adjacent crayfish swimmerets of approximately 0.25 of the period is more hydrodynamically efficient than being in phase (0) or 0.75 of the cycle period regardless of speed, size of the crayfish, or swimmeret cycling frequency. Spardy and Lewis[40] have subsequently extended the model of Zhang et al for control of crayfish swimmerets to include effects of neighboring neural circuits that are beyond the nearest neighbor. While the nearest neighbor circuits have the dominant effect of setting the phase difference to 25%, the model showed that the longer neighbors can also have a small effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Zhang et al [23] used computational fluid dynamics in conjunction with a neural model of CPG circuits to show that a locked phase difference between adjacent crayfish swimmerets of approximately 0.25 of the period is more hydrodynamically efficient than being in-phase (0) or 0.75 of the cycle period regardless of speed, size of the crayfish, or swimmeret cycling frequency. Spardy and Lewis [36] have subsequently extended the model of Zhang et al for control of crayfish swimmerets to include the effects of neighbouring neural circuits that are beyond the nearest neighbour. While the nearest neighbour circuits have the dominant effect of setting the phase difference to 25%, the model showed that the longer neighbours can also have a small effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, modeling studies have shown that the DSC input from the immediate neighboring ganglion is crucial to maintain the phase lag. With only long-range DSC input, phase lags decreased (Spardy and Lewis, 2018).…”
Section: Discussionmentioning
confidence: 99%